Effect of subacute toxicity of mosquito coil smoke inhalation on lung histology and blood hematology parameters in Wistar rats - Mulyati Sri Rahayu; Sri Wahyuni (Universitas Nahdlatul Ulama Surabaya, 2025)
Mosquito coils are made from incense products and are designed to repel insects using pyrethrins and pyrethroids as their main active ingredients. However, the use of these coils poses significant public health and ecological risks due to the emitted toxic fumes. These fumes can have long-term damaging effects on humans and the environment. This study aimed to investigate the effects of various durations of subacute exposure to mosquito coil smoke (MCS) on lung histology and blood hematology in white male Wistar rats (Rattus norvegicus). Rats were divided into four groups (n = 6): control; P1, P2, and P3, exposed to MCS for 5, 7, and 9 h per day, respectively, for 21 days. Hematological blood analyses (red cell count (RBC), hemoglobin (Hb), and hematocrit (Hct)) were performed, and lung histopathology was evaluated using Manja Roenigk's criteria. The group exposed to MCS for 9 h/day showed a significant decrease in mean body weight (185.00 ± 9.59) (p = 0.008) compared with the control group. All treated groups had normal Hb and Hct levels and RBC indices, with no significant differences compared with the control group. The 9-hour exposure group had significantly lower lung weights than the control group (p<0.05), and all treatment groups showed significant differences in lung weight (p<0.05). Histopathological analysis revealed significant loss of alveolar septal integrity, leading to alveolar lumen rupture and development of emphysema. This study provides clear evidence of emphysema due to subacute allethrin-based MCS inhalation, although it did not affect hematological parameters in rats.